Pelatihan Pembuatan Kerajinan dari Manik-manik untuk Meningkatkan Kreativitas Anak-anak di Rumah Yoel - Mery Hanawidyatmi; Isma’il Amin Sholihin; Nur Laela Rohmayati; Siti Aniroh; Feby Irnadia Ifada; Dian Wulandari; Ignatia Esti Sumarah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to: Provide assistance to the children of the Rumah Yoel Community to build entrepreneurial skills using the main materials of beads and string which are cheap and easy to obtain. Building children's mindset to become independent, creative and highly competitive individuals in society. This research uses descriptive qualitative methods. The research subjects were the children of the Rumah Yoel Community. The training participants were 16 children in the Rumah Yoel Community. The meeting took place over three meetings with stages, 1) observation and interviews with the Rumah Yoel Community administrators, 2) observation and interviews with the children with the assistance of Rumah Yoel Community teachers, 3) skills training for the Rumah Yoel Community children. Training is evaluated using the results of service video comments, pretest and posttest. Results of the service: 1) researchers were able to train children's skills in making crafts through creativity using the main materials of beads and rope so that children were able to make key chains, bracelets, headbands and rings. Second; 2) researchers invite children to use packaging for their work so that it has economic value. 3) Researchers are able to invite children to take part in activities according to the procedures directed in making works using practical methods. 4) researchers provide skills for the children of the Rumah Yoel community because by training them to be creative with beads it can motivate them to become entrepreneurs from an early age to help their parents.